Risk assessment of exposure to multiple mycotoxins in food - Viegas, Susana (2012)
Moulds may produce a diversity of toxins such as aflatoxins, ochratoxins, trichothecenes, zearalenone, fumonisins and others. Although toxicological, environmental and epidemiological studies have addressed the problem of these toxins one by one, more than one mycotoxin are found usually in the same contaminated food. Risk assessment for humans potentially exposed to multimycotoxins suffers very much from the lack of adequate food consumption data. Furthermore, for a given mycotoxin, synergism and antagonism with other mycotoxins, found in the same food commodities, are not taken into account. Aflatoxin B1 and ochratoxin A belong to the most frequently occurring mycotoxins. This has repeatedly been demonstrated, however, normally, the risk resulting from their simultaneous occurrence is not considered. A descriptive study was developed to monitor air fungal contamination in one hospital food unit.